An OIE-Approved Reference Laboratory for Veterinary Mycobacteriology in Iran - K Tadayon; K Forbes; N Mosavari; A Thomson; F Sadeghi (Tehran University of Medical Sciences, 2005)
Body Mycobacterial diseases are an important group of animal infections, which have tremendous economic and public health ramifications. Bovine tuberculosis and paratuberculosis, both identified years ago, have no effective vaccine or treatment controls in farm animals. In Asia, there are only seven countries where test-and-slaughter schemes are currently ongoing to control bovine tuberculosis. On the other hand, among five mycobacteriology reference laboratories, licensed by OIE, in the world, none is located in Asia. Iran has proved to have an efficient control program against tuberculosis in cattle since the 1960s. While the locally made PPD tuberculins required for the testing of cattle are apparently useful in the Iranian scheme, there is no organised establishment in Iran to support the control programme with bacteriological services. This presentation considers the needs and potentials of a reference laboratory facility in Iran.